Inquéritos policiais de homicídio no Espírito Santo : uma análise indiciária das dificuldades através de estudos de casos - Gusmão Neto, Ayrton (2019)
The present work sought to analyze in depth a certain number of cases of consummated homicides in the state of Espírito Santo in the year of 2012, in the metropolitan region of Grande Vitória. The temporal cut was due to the possibility of access to the police inquiries from the Civil Police this year. An overview of this investigations in Brazil is presented, specially about homicides and from the state of Espírito Santo, followed by a detailed analyze of eight of them, chosen in a random way, seeking to highlight specificities and particularities in order to determine hypotheses, especially in relation to the difficulties faced by the police when working with this type of crime. This is because common problems regarding homicide crimes are the difficulty of investigation and evidence gathering for example. In this way, through the analysis of the police inquiries we try to answer: what problems can we verify? What problems do the police routinely have to deal with and how do they generally disrupt the investigations? Also, are discussed concepts such as biopolitics, criminalization of poverty, criminal subjection, among others, in order to to discuss the data found with the theories of the authors of these concepts. The main results, which are in agreement with the research hypotheses, are related to the difficulty of collaboration on the part of the witnesses, the need to work to a great extent with witness evidence, and, finally, inefficiency and difficulty of communication by the Technical Police. The research had of the Coordination for the Improvement of Higher Education Personnel (in portuguese, CAPES) through the grant of financial assistance and is linked to research “Study of the Dynamics of the standards of homicide in Espírito Santo in areas of action of the Present State Program: Serra and Cariacica”; and “Study of the Dynamics of homicide patterns in Espírito Santo in areas of Present State Program: Vitória and Vila Velha”, that received financial support from the Support to the Research of Espírito Santo (in portuguese, FAPES), and was coordinated by the teacher Márcia Barros Rodrigues Ferreira.